Tocilizumab for Treatment of Mechanically Ventilated Patients With COVID-19. (11th July 2020) - Somers, Emily C; Eschenauer, Gregory A; Troost, Jonathan P; Golob, Jonathan L; Gandhi, Tejal N; Wang, Lu; Zhou, Nina; Petty, Lindsay A; Baang, Ji Hoon; Dillman, Nicholas O; Frame, David; Gregg, Kevin S; et al.
Abstract: Background: Severe coronavirus disease 2019 (COVID-19) can manifest in rapid decompensation and respiratory failure with elevated inflammatory markers, consistent with cytokine release syndrome for which IL-6 blockade is an approved treatment. Methods: We assessed effectiveness and safety of IL-6 blockade with tocilizumab in a single-center cohort of patients with COVID-19 requiring mechanical ventilation. The primary endpoint was survival probability postintubation; secondary analyses included an ordinal illness severity scale integrating superinfections. Outcomes in patients who received tocilizumab compared with tocilizumab-untreated controls were evaluated using multivariable Cox regression with propensity score inverse probability of treatment weighting (IPTW). Results: 154 patients were included, of whom 78 received tocilizumab and 76 did not. Median follow-up was 47 days (range, 28–67). Baseline characteristics were similar between groups, although tocilizumab-treated patients were younger (mean: 55 vs 60 years), less likely to have chronic pulmonary disease (10% vs 28%), and had lower D-dimer values at time of intubation (median: 2.4 vs 6.5 mg/dL). In IPTW-adjusted models, tocilizumab was associated with a 45% reduction in hazard of death (HR, .55; 95% CI, .33–.90) and improved status on the ordinal outcome scale [OR per 1-level increase, .58; .36–.94). Although tocilizumab was associated with an increased proportion of patients with superinfections (54% vs 26%; P < .001), there was no difference in 28-day case fatality rate among tocilizumab-treated patients with versus without superinfection (22% vs 15%; P = .42). Staphylococcus aureus accounted for 50% of bacterial pneumonia. Conclusions: In this cohort of mechanically ventilated COVID-19 patients, tocilizumab was associated with lower mortality despite higher superinfection occurrence. Abstract : In this observational, controlled study of 154 patients with severe COVID-19 illness requiring mechanical ventilation, tocilizumab was associated with a 45% reduction in the risk of death, despite twice the frequency of superinfection (54% vs 26%).